Higher Education Instructors Perception and Practice of Active Learning and Continuous Assessment Techniques: The Case of Jimma University - W. M. Tarekegne (University of Sofia, 2019)
This article examines instructors perception and practice on active learning and continuous assessment in higher education of Ethiopia. Data were collected from participants (instructors, deans, department heads, and students) through questionnaires, interview, focus group discussion and observation. The results show that instructors perceive positively for these two constructivist strategies. In addition, even though some instructors are trying to use few active learning and continuous assessment methods in their classrooms the majority of them are not practicing as expected. The factors affecting successful implementation of active learning and continuous assessment include teachers commitment, students attitude, and institutional problems, lack of resources, large class size, and high teaching load.